DAYA SAING UNGGUL INSTITUSI PASCASARJANA PTS DI JAKARTA: ANALISIS FOKUS PADA KONSUMEN DAN KORELASI DIMENSI YANG SUPERIOR - Wilhelmus Hary Susilo (Universitas Bunda Mulia, 2016)
A concept that developed from Marketing 3.0 that examine the influence of customer orientation that development the building of Institutional character as build a uniqe and authentic differentiation variable with the level of competitiveness of institutions of higher education as dependent variable. The findings of the research showed positive and significant influence of customer orientation variabel and building character on institutional competitiveness level of variable (P value .002, .002 and .00) . While significant effects also occurs between variable customers orientatition and building character of institution together on the level of competitiveness of institutions simultaneously. Furthermore the relationship dimention the most powerful variable is a responsibility dimension of quality management and task design with r (er) value= .816**.Key words: Organizational Competitiveness. Marketing 3.0, Superior Dimensions.